You know that we have to simplify the algebra equation, so first you have to combine x and 2x. X + 2x equals to 3x. Now that we combined x and 2x which makes 3x, we have to do 7 and -8. 7 + -8 which equals to -1. Therefore, the answer to this algebra equation is 3x + -1.
So first you have to move the -2 over to the opposite side.
8(9x-4)=3+2+2
Then you can simplify the right side
8(9x-4)=7
Then you distribute
8*9x=72x
8*-4=-32
so now you have...
72x-32=7
Then you move the 37 over
72x=39
Then you divide by 72 to isolate x
x=39/72 or x= 13/24 or <span>x=0.54167</span>
The answer is -10x^3+23x^2-24x+18
Answer:
- 10 - (-20 + 5)
Step-by-step explanation:
- 10 - (-20 + 5)
- 10 - (-15) = -10 + 15
-10 + 15 = 5
have a nice day and mark me brainliest! :)